Fuelwood Production Potential in India Through Short Rotation, Intensive Culture (SRIC) Systems Applied to Tree Growing for Fuelwood on Reduced Land Area or on Wasteland Sites - Dogra, P. D. (Indian Forester, 1989)
Forestry research is typically a long term effort. Some problems of forestry like fuelwood production cannot be solved entIrely by long effort research programmes. Intensification of developmental research on short rotation intensive culture of trees (SRIC systems) for large scale fuelwood production is therefore suggested involving the unified efforts of several disciplines including managfment and economic analysis for cost-effective feasibility. It is further suggested that SRIC system be further modified to be adopted for use on various type of wasteland.